Intergroup relations, acculturation orientations, and adaptation of Turkish immigrant descent parents across Europe - Guerra, R.; Broekhuizen, M.; Francot, R.; Kolancali, P. (Cultural Diversity and Ethnic Minority Psychology, 2025)
Objectives: The current research examines whether Turkish immigrant descent parents’ perceived discrimination, intergroup contact with the majority, nonimmigrant society, and acculturation orientations are related to their psychological and sociocultural adaptation (i.e., life satisfaction and parental self-efficacy). Additionally, it explores potential differences in these relations between three European countries. Method: Participants were parents (Mage = 38.05, SD = 5.81, 85.3%–99.6% female) of Turkish origin from England (n = 293), Germany (n = 338), and the Netherlands (n = 247) who participated in a large-scale structured interview study. Results: As predicted, perceived discrimination was negatively associated with Turkish immigrant descent parents’ psychological adaptation, although not with sociocultural adaptation. Positive contact with the majority, nonimmigrant society positively predicted both psychological and sociocultural adaptation. Contrary to the expected, only desire for contact was positively associated with both psychological and sociocultural adaptation, whereas culture and language adoption was not related to adaptation. Conclusions: Together these findings highlight the importance of majority, nonimmigrant societies fostering conditions and policies that promote opportunities for harmonious interactions between immigrant/immigrant descendants and majority, and nonimmigrant populations.